Porphyrin biosynthesis in rhodopseudomonas palustris-V. Purification of porphyrinogen decarboxylase and some unusual properties - Koopmann, G.E. (1986)
1. 1. Uroporphyrinogen decarboxylase (EC 4.1.1.37) has been purified 16-fold from Rp. palustris to a specific activity of 210 nmol of total decarboxylated porphyrinogens III formed/hr per mg of protein and about 50% yield. The Rp. palustris enzyme exhibits some unusual properties as compared with URO-D from other sources. 2. 2. The purified enzyme is a monomer with a molecular weight of ∼46,000, an isoelectric point of 4.6 and an optimum pH of 6.9 and 6.8 with urogen III and I substrate. Neither GSH nor EDTA seem to be necessary for activity, and the decarboxylation rate and the distribution of the reaction products was not affected either by the presence or absence of oxygen. 3. 3. The Rp. palustris enzyme is a thermo-stable protein, heating at 60°C for 15 min enhanced several times activity. This is the first time that the heat treatment is included as one of the steps to purify URO-D. 4. 4. Thermal activation followed an identical profile using either substrate. The ratios of specific activity for the type III and I isomer of urogen remained constant throughout the purification. These findings are indicating that a single enzyme catalyzes the four decarboxylations occurring from urogen to coprogen. 5. 5. Kinetic data employing urogen III and I as substrate showed that the pattern of accumulated intermediates was rather different depending on whether type III or I isomer was used. 6. 6. While decarboxylation of urogen III responds to the usual scheme: A figure is presented where v1≫v2 and decarboxylation of heptagen III is the rate-controlling step. 7. 7. Decarboxylation of urogen I revealed a completely different and characteristic picture fitting the scheme: A figure is presented where again v′1≫v′2 and the removal of the final carboxyl group from pentagen I becomes the rate-limiting step. © 1986.